Catholic Responses to AIDS in Southern Africa - Bate, Stuart C.; Munro, Alison; OFM, Wilfred; CSsR, Kevin; Stark, Ruth; Wilke, Marisa; Rakoczy, Susan; OMI, Raymond; HF, Melanie; SJ, Michael; SJ, Agbonkhianmeghe; SCJ, Chris; et al. (Southern African Catholic Bishops’ Conference (SACBC); Grace & Truth St Josephs Cedara, 2014)
During 2013, a conference on the response of the Catholic Church to HIV and AIDS was held at St Joseph's Theological Institute, Cedara KwaZulu-Natal. This book brings together papers presented at the conference together with some significant documents of the Catholic Magisterium in Southern Africa and beyond written during the course of the last 30 years. The Catholic Church in Southern Africa has been one of the principal players in the response to the HIV and AIDS crisis. From a relatively slow beginning in the 1980s it had become a major provider of health care and information on HIV prevention by the early 21st century. This book examines both the pastoral outreach and the theological motivation for this involvement
Free